The Effectiveness of Mediation in Civil Cases at District Courts: A Legal Review of PERMA No. 1 of 2016 - Anggi Sri Haryati Simarmata; Bengawan Reno Falah Aziz (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the effectiveness of court-annexed mediation in civil cases within Indonesian district courts through a normative juridical analysis of Supreme Court Regulation Number 1 of 2016. Employing doctrinal legal research, the study analyzes statutory provisions, legal doctrines, and scholarly literature to assess the coherence between normative design and its conceptual implementation. The findings indicate that the regulation has introduced significant procedural improvements, including clearer obligations, structured timelines, and strengthened roles for certified mediators. However, effectiveness remains constrained by ambiguities in the operationalization of good faith, inconsistencies in judicial interpretation, and limited institutional capacity. Cultural resistance among disputing parties and legal practitioners further weakens the practical realization of mediation objectives. The study highlights that legal effectiveness is contingent upon the interaction between normative clarity, institutional support, and legal culture. It argues for a holistic reform approach encompassing regulatory refinement, capacity building, and public legal awareness. Strengthening these dimensions is essential to position mediation as a credible and efficient mechanism for civil dispute resolution within the Indonesian judicial system